Applications of stiffness-based evaluation method to element importance of truss systems - Cai, Jianguo; Jia, Wenwen; Feng, Jian; Wang, Fang; Xu, Yixiang (Journal of Civil Engineering and Management, 2017)
Two structural performance indexes, making use of eigenvalues of stiffness matrix, are presented in the study for the evaluation of element importance in the progressive collapse analysis of space trusses. Both indexes are based on the consensus that the element transferring higher loads in the load path is generally more important in the structural system. The first index is formulated as change of the smallest stiffness after removal of specific element, and the second index is defined as determinant of the stiffness matrix. Several simple numerical examples are presented to investigate performance of the proposed indexes; and finally, a square pyramid space grid system is studied as an illustrative example.